(untitled) (Bulletin of the International Association for Paleodontology, 2021)
There are meanings which were [are] attributed to the archetypal image of the tooth, honouring how dynamic operations of the biological (chemical and physiological characteristics), emotional, and behavioural aspects of its existence and organic manifestation impacted the understandings that some ethnic communities, ingrained in their own ecological, geographic, religious, historic, and cultural factors, built and developed through their approximations to teeth. That can be possibly seen as scaffolding the innumerable, stable and/or modified symbolic representations that constitute the emerging narratives modern humans manifest and exchange when having the tooth as the object of their current experience and enquiry. It discusses individual, collective, and transpersonal states of feeling and reasoning that analyse the possession and the observation of teeth and the phenomena related to their utility, appearance, state of wear, and identitarian judgements that can be drawn from their materiality. Hence, this literature review discusses how the practise and/or attribution of rituals for modification and/or mutilation of teeth, socioeconomic expectations, cultural meanings, self-identity information, dietary styles, and crimes that surround the human dentition have occurred and insist to occur throughout the conscious and/or unconscious transmission of ideas and ideals that are attached to the image of the tooth, revealing a certain common yet transformed knowledge between traditional and modern societies.